Information Technology Development's Impact On Library Services - fauziyyah, syifaa; Febriyanti, Rahma Ayu; Nurtino, Tio; Huzaifah, Muhamad Lutfi; Kusumawardhani, Dhiyah Ayu Rini (Pandawan Sejahtera Indonesia, 2023)
The purpose of this study is to find out how library services will be affected by advances in information technology. This research examines the various services offered by the library as well as the facilities and technology used there. A descriptive qualitative method was used in this study. Direct observation and interviews were used as data collection methods in this study. In addition, there was an opportunity for the researchers to ask some questions regarding the research that had been conducted. The library director participated in this research. The services provided by the library are a combination of manual and technological services. The main way information technology affects library services is by making it easier for library staff to do their jobs, attracting more visitors, and modernizing the facilities offered by the library.